Molecular Diversity And Gene Flow Among Botryodiplodia Theobromae Populations In Pear Using Rapd Markers (Applied Biological Research, 2012)
Different populations of Botryodiplodia theobromae causing pear die-back  and bark canker in Punjab, India were analyzed for their diversity at  molecular level, gene flow and heterogeneity. Molecular diversity was  assessed on the basis of allele frequencies of randomly amplified poly morphic DNA (RAPD) primers using POPGENE software. Allele  frequency ranged from 0.0 to 1.0 in 3 populations of B. theobromae. Mean  genetic diversities within population (HS) varied from 0.25 to 0.80  indicating a high diversity. Molecular diversity across the populations  ranged from 0.09 to 0.50 with a mean of 0.39; and differed significantly  from mean HS (0.27). Diversity indices of RAPD loci varied from very low  (< 0.09) to very high HS values (>0.50) across the populations (GST) with a  mean GST of 0.30. Lower GST values of 0.019, 0.036,0.052, 0.074 and 0.097  were observed at S116, S1109, S1120, S1118 and S1110 loci, respectively,  depicting high genetic diversity among all the isolates. However, at S111  locus the GST value was 0.80 indicating low diversity in population at this  locus. Out of 51 loci 33 showed gene flow (Nm) < 1 indicating high genetic differentiation within the population, while rest with Nm >1 had frequent  gene flow across the populations of B. theobromae. Pair-wise comparison  (GST) values among all the loci ranged from 0.22 to 0.35 revealing low  genetic differentiation among the populations. The observed high  molecular diversity (HS) within the population suggested that B.  theobromae variability was high in Punjab. The RAPD-based  dendrorgam divided isolates into 3 major clusters at 65% similarity  coefficient. In general, 20-25% similarity was observed among all the  isolates of B. theobromae in Punjab.
Keywords: Bark canker; Botryodiplodia theobromae; die-back; gene flow; molecular diversity; pear; RAPD markers